Cardiac autonomic and salivary responses to a repeated training bout in elite swimmers - Edmonds, R.; Leicht, A.; Burkett, B.; McKean, M. (Sports, 2016)
This study examined the acute training responses of heart rate variability (HRV) and salivary biomarkers (immunoglobulin A and alpha-amylase) following a standardised training bout in Paralympic swimmers. Changes in HRV, sIgA and sAA were documented Monday morning, Monday afternoon and Tuesday morning over a 14-week monitoring period leading into international competition. Magnitude based inferences with effect sizes (ES) were used to assess the practical significance of changes each week. Normal training responses elicited increases in HR, a1, sAA and sIgA, accompanied by decreases in HF(nu), standard deviation of instantaneous RR variability (SD1) and the root mean square of successive differences (RMSSD) from Monday morning to Monday afternoon, and to Tuesday morning with similar week to week responses for most variables. Changes in RMSSD from Monday a.m. to p.m. were likely smaller (less negative) for Week 7 (78/18/3, ES = 0.40) following a competition weekend with similar changes observed from Monday a.m. to Tuesday a.m. (90/5/5, ES = 1.30). In contrast, the change in sAA from Monday a.m. to p.m. was very likely less (more negative) at Week 7 (0/0/99, ES = -2.46), with similar changes observed from Monday a.m. to Tuesday a.m. (0/0/99, ES = -4.69). During the taper period, there were also likely increases in parasympathetic modulations (RMSSD, Weeks 12-14) along with increased immune function (sIgA, Week 13) that demonstrated a favourable state of athlete preparedness. Used together, HRV and sAA provide coaches with valuable information regarding physiological changes in response to training and competition.